Constructing an Optimal Investment Portfolio for the Bank of Lithuania - Galinienė, Birutė; Stravinskytė, Justina (Ekonomika, 2016)
The main goal of this article is to illustrate the strategy, devised to improve the effectiveness of utilizing the financial assets, or in this case, the official international reserves, belonging to the Bank of Lithuania. In Lithuania, the value of financial assets as a percentage of total state assets has doubled in the span of 10 years. Moreover, a strong correlation between the real GDP growth and the Bank of Lithuania’s financial assets/profitability implies that the effectiveness of financial assets management has a nationally wide impact. Unfortunately, the Bank’s profit/invested value indicator has reached a record low in 2012–2013, which resulted in the whole bank’s profit being absorbed into the state’s budget (as opposed to 70 % of it). Such signs meant that the previous investment strategy has become ineffective and needed changes. To highlight the necessary changes, the authors conduct a practical research and construct the optimal investment portfolio, according to the goals and variables given by the guidelines, proposed by Bank of Lithuania. The size of the portfolio is 4,14 bn euros, and the maximum loss per year (VaR) allowed is -100 M euro/year, as stated by the Bank of Lithuania’s risk budget limit. The authors also focus on the issue of increased currency risk after investing in volatile share indices and whether hedging against it with Forex spot transactions is beneficial. The result of the research is an optimal portfolio, consisting of 9,85 percent of risk-free assets and 90,15 percent of risky assets. Hedging against currency risk in this case is an ultimately beneficial course of action, yielding an increase of annual returns by 0,3 percent, which translates to +12,3 mln euros. Finally, the portfolio is flexible and simple to reshape into a less risky variant, if the institution predicts the dangers of possible future economic downfalls. This research was further used in a broader paper whose goal was to analyse and assess the effectiveness of currently employed assets’ management strategies in Lithuania.